2016
DOI: 10.18632/oncotarget.11694
|View full text |Cite
|
Sign up to set email alerts
|

eIF4E promotes tumorigenesis and modulates chemosensitivity to cisplatin in esophageal squamous cell carcinoma

Abstract: Patients with esophageal squamous cell cancer are often diagnosed with advanced diseases that respond poorly to chemotherapy. Overexpression of eIF4E leads to enhance the translation of key malignancy-related proteins and enabling tumor growth and chemoresistance in a variety of human malignancies, but whether it has a role in ESCC remains obscure. We hypothesized that eIF4E promoted ESCC tumorigenesis and facilitated the development of acquired resistance to the cisplatin-based chemotherapy. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In recent studies, the phosphorylation of AKT was shown correlated with poor prognosis in ESCC (31,32). AKT was responsible for the cisplatin resistance, and could promote metastasis of ESCC by targeting epithelial-mesenchymal transition (33)(34)(35). mTOR activation was able to also prcomote the cell proliferation and tumor progression of ESCC (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the phosphorylation of AKT was shown correlated with poor prognosis in ESCC (31,32). AKT was responsible for the cisplatin resistance, and could promote metastasis of ESCC by targeting epithelial-mesenchymal transition (33)(34)(35). mTOR activation was able to also prcomote the cell proliferation and tumor progression of ESCC (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Housekeeping mRNAs, for example, cytoskeleton proteins, require a low level of eIF4E, whereas proto-oncogenic and prosurvival proteins such as c-Myc, cyclin D1, Pim-1, survivin, Bcl-2, VEGF have a much higher dependency on eIF4E for translation [11,12]. These mRNAs are termed as 'weak mRNAs' and are greatly influenced by an increase in eIF4E levels, observed in 30% of human cancers [13][14][15]. The availability of eIF4E is regulated by 4E-binding proteins, which compete with eIF4G for a common surface to bind to eIF4E [4,16,17].…”
Section: Dual Targeting Of Mnks Reviewmentioning
confidence: 99%
“…DDP is a first-line drug in the treatment for ESCC, and DDP resistance remains a serious challenge. A previous study conducted by the present research team indicated that the expression of CtBP2 was upregulated in ESCC tissues compared with adjacent non-tumorous tissues (17). However, the effect of CtBP2 on the susceptibility of ESCC cells to DDP was unclear.…”
Section: Discussionmentioning
confidence: 69%
“…Cisplatin (DDP) is a first-line drug in the treatment for ESCC, and the development of DDP resistance in ESCC cells is the main cause of chemotherapy failure (14,15). The effectiveness of chemotherapy depends on the sensitivity of the tumor cells to chemotherapy drugs (16), and ESCC usually exhibits a high resistance to chemotherapy (17,18). Therefore, the identification of oncogenes that may be targeted to combat resistance is likely to be a great benefit to clinical practice.…”
Section: Introductionmentioning
confidence: 99%